Clay mineralogy indicates the muddy sediment provenance in the estuarine-inner shelf of the East China Sea. (February 2018) - Zhao, Yifei; Zou, Xinqing; Liu, Qing; Wang, Chenglong; Ge, Chendong; Xu, Min
Graphical abstract: Highlights: High-resolution clay minerals record in the estuarine-inner shelf of the ECS over the past 100 years. The sediments on the estuarine-inner shelf of the ECS are a mixture of provenances from the Yangtze and Yellow Rivers as well as smaller rivers. The river sediment loads, East Asian winter monsoon and coastal current play a critical role for sediment transport in the estuarine-inner shelf of the ECS. Abstract: The estuarine-inner shelf mud regions of the East China Sea (ECS) are valuable for studying the source-to-sink processes of fluvial sediments deposited since the Holocene. In this study, we present evidence of the provenance and environmental evolution of two cores (S5-2 and JC07) from the estuarine-inner shelf regions of the ECS over the past 100 years based on 210 Pb dating, high-resolution grain size measurements and clay mineral analyses. The results indicate that the clay mineral assemblages of cores S5-2 and JC07 are dominated by illite, followed by kaolinite and chlorite, and present scarce amounts of smectite. A comparison of these clay mineral assemblages with several major sources reveals that the fine sediments on the estuarine-inner shelf of the ECS represent a mixture of provenances associated with the Yangtze and Yellow Rivers, as well as smaller rivers. However, the contribution of each provenance has varied greatly over the past hundred years, as indicated by the down-core variability due to strong sediment reworking and transport on the inner shelf and the reduction of the sediment load from the Yangtze River basin. In the mud region of the Yangtze River estuary, the sediment from 1930 to 1956 was primarily derived from the Yangtze River, although the Yellow River was also an important influence. From 1956 to 2013, the Yellow River contribution decreased, whereas the Yangtze River contribution correspondingly increased. In the Zhe-Min mud region, the Yangtze River contributed more sediment than did other rivers from 1910 to 1950; however, the Yangtze River contribution gradually decreased from 1950 to 2013. Moreover, the other small rivers accounted for minor contributions, and the East Asian winter monsoon (EAWM) played an important role in the sediment transport process in the ECS. Our results indicate that the weakening/strengthening of the EAWM and a decrease in the sediment load of the Yangtze River influenced the transport and fate of sediment on the estuarine-inner shelf of the ECS.